2021
DOI: 10.3390/jpm11010036
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model and Risk Factors for Case Fatality of COVID-19

Abstract: This study aimed to create an individualized analysis model of the risk of intensive care unit (ICU) admission or death for coronavirus disease 2019 (COVID-19) patients as a tool for the rapid clinical management of hospitalized patients in order to achieve a resilience of medical resources. This is an observational, analytical, retrospective cohort study with longitudinal follow-up. Data were collected from the medical records of 3489 patients diagnosed with COVID-19 using RT-qPCR in the period of highest com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 54 publications
(50 reference statements)
1
25
0
Order By: Relevance
“…They have been reported to be useful for monitoring and predicting disease outcome and prognosis [20,21]. A recently published study [22] created a model for individualized analysis of the risk of admission or death of patients with COVID-19 in an intensive care unit (ICU). This could be a useful tool for rapid clinical management and for achieving resilience of medical resources.…”
Section: Introductionmentioning
confidence: 99%
“…They have been reported to be useful for monitoring and predicting disease outcome and prognosis [20,21]. A recently published study [22] created a model for individualized analysis of the risk of admission or death of patients with COVID-19 in an intensive care unit (ICU). This could be a useful tool for rapid clinical management and for achieving resilience of medical resources.…”
Section: Introductionmentioning
confidence: 99%
“…This silent hypoxemia is not characterized by typical respiratory distress in critically ill patients, but it may be dangerous if it is not sooner detected as a prompt deterioration can occur without noticing [137]. In fact, previous studies have demonstrated the association between hypoxemia with fatal outcomes in patients with COVID-19 [138].…”
Section: Role Of Hbot In the Covid-19 Pandemicmentioning
confidence: 97%
“…This silent hypoxemia is not characterized by typical respiratory distress in critically ill patients, but it may be dangerous if it is not sooner detected as a prompt deterioration can occur without noticing [ 137 ]. In fact, previous studies have demonstrated the association between hypoxemia with fatal outcomes in patients with COVID-19 [ 138 ]. In the same manner, physicians observed that patients exhibit hypoxemia without dyspnea, being crucial to find care solutions to anticipate a problem with more patients at important risk [ 139 ].…”
Section: Translational and Potential Applications Of Hbotmentioning
confidence: 99%
“…However, if the immune response fails, SARS-CoV-2 may be able to disseminate throughout the organism, promoting an aberrant immune response with uncontrolled cytokine production (a so-called “cytokine storm”), acute respiratory-distress syndrome (ARDS), and multiorgan failure [ 33 ]. In fact, immune cells, as well as inflammatory components, have been proven to be valuable markers for predicting COVID-19 fatality [ 34 ]. Therefore, it is crucial to ensure an adequate immune response to prevent or mitigate SARS-CoV-2 infection.…”
Section: Structure and Pathogenesis Of Sars-cov-2mentioning
confidence: 99%